Calcium phosphate nanoparticles prepared via solid-state route - N. Natasha, A.; Ramesh, S.; Y. Tan, C. (International Journal of Engineering and Technology, 2018)
To date, the direction of bioceramic research is focused on the improvement of the mechanical performance and biological properties of existing bioactive ceramics particularly HA. Hence, the synthesis of crystalline HA nanoparticles with expected microstructure is of   primary importance because the process directly relates to the phase purity, morphology, and particle size of the final HA particles. In this work, a simple and cost-effective technique, solid state reaction method was successfully employed to synthesize highly crystalline, high purity and single phase nanostructured hydroxyapatite powder using waste eggshells (HA-Es). The process involved mixing calcined eggshell powder and dicalcium hydrogen phosphate di-hydrate followed by a heat treatment at 800 °C for 5 hours. The resultant flower-like nanostructure HA powder is composed of leaf-like flakes having 100-200 nm width and crystallite size calculated using XRD data of ~56.21 nm.